2021
DOI: 10.3390/app11030989
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Glucose to 5-Hydroxymethylfurfural, Levulinic Acid, and Formic Acid in 1,3-Dibutyl-2-(2-butoxyphenyl)-4,5-diphenylimidazolium Iodide-Based Ionic Liquid

Abstract: The separation process between 5-hydroxymethylfurfural (HMF) and trace glucose in glucose conversion is important in the biphasic system (aqueous–organic phase), due to the partial solubility property of HMF in water. In addition, the yield of HMF via the dehydration reaction of glucose in water is low (under 50%) with the use of Brønsted acid as a catalyst. Therefore, this study was conducted to optimize the production and separation of products by using a new hydrophobic ionic liquid (IL), which is more sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…cellulose and hemicellulose, are also valuable sources of compounds for the development of bio-based ILs when converted into smaller molecules such as formic acid, acetic acid, levulinic acid, furfural and hydroxymethyl furfural. [33][34][35][36] While formate and acetate ILs have been known for more than twenty years, the utilization of the other mentioned platform chemicals for ILs preparation is far more recent. In particular, for furfural and hydroxymethyl furfural a very limited number of studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…cellulose and hemicellulose, are also valuable sources of compounds for the development of bio-based ILs when converted into smaller molecules such as formic acid, acetic acid, levulinic acid, furfural and hydroxymethyl furfural. [33][34][35][36] While formate and acetate ILs have been known for more than twenty years, the utilization of the other mentioned platform chemicals for ILs preparation is far more recent. In particular, for furfural and hydroxymethyl furfural a very limited number of studies have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Scheme depicts the most predominant reaction mechanisms for Brønsted acid-catalyzed dehydration of glucose to HMF, including a direct dehydration pathway (B), as well as cyclic (A), and acyclic (C) mechanisms with the intermediate formation of fructose. Although extensive evidence supporting acyclic ,, and cyclic ,,, pathways has been presented, it is generally agreed that the specific reaction mechanism is determined by the reaction conditions, particularly the choice of solvent. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…Xiang et al reported that the production of 5-HMF using only water as the solvent did not significantly improve the conversion of glucose to 5-HMF. Dehydrating agents such as Lewis acid or Brønsted acid sites are required to promote sugar dehydration to 5-HMF [42].…”
Section: Effect Of Reaction Time and Glucose: Lttm: Water Ratiomentioning
confidence: 99%